Let us analyze in more detail the equation of a circle of radius r centered at the point \(C\left( {{x_0},{y_0}} \right)\):
The equation of this circle is
\[{\left( {x  {x_0}} \right)^2} + {\left( {y  {y_0}} \right)^2} = {r^2}\]
If we square and expand, we have the following:
\[\begin{align}&{x^2} + {x_0}^2  2x{x_0} + {y^2} + {y_0}^2  2y{y_0} = {r^2}\\&\Rightarrow \,\,\,{x^2} + {y^2}  2{x_0}x  2{y_0}y + {x_0}^2 + {y_0}^2  {r^2} = 0\end{align}\]
We see that there is an \({x^2}\) term, a \({y^2}\) term, a term which is linear in x, a term which is linear in y, and a constant term. Taking cue from this, we can write the general equation of a circle as follows:
\[\underbrace {{x^2} + {y^2}}_{\scriptstyle{\rm{Square \,\,terms}}\atop{\scriptstyle{\rm{with \,\,equal}}\atop\scriptstyle{\rm{coefficients}}}} + \underbrace {2gx + 2fy}_{{\rm{Linear terms}}} + \underbrace c_{\scriptstyle{\rm{Constant}}\atop\scriptstyle{\rm{term}}} = 0\]
Why have we taken the coefficients of x and y as 2g and 2f, rather than, say, g and f? These and other aspects of this general equation will become clearer when you delve deeper into this analysis at a later stage.
To summarize:

The equation of a circle with center \(\left( {{x_0},{y_0}} \right)\) and radius r can be written as
\[{\left( {x  {x_0}} \right)^2} + {\left( {y  {y_0}} \right)^2} = {r^2}\]

The general equation of a circle can be written as
\[{x^2} + {y^2} + 2gx + 2fy + c = 0\]
If we rearrange the first equation into the general form, we have:
\[\begin{array}{l}{x^2} + {y^2} + \left( {  2{x_0}} \right)x + \left( {  2{y_0}} \right)y\\ \,\,\,\,\,\;\;\;\;\;\;\;\;\;\; + \left( {{x_0}^2 + {y_0}^2  {r^2}} \right) = 0\end{array}\]
If we compare this with the general form a circle’s equation, we have:
\[\begin{align}&  2{x_0} = 2g,\,\,\,  2{y_0} = 2f,\,\,\,\left( {{x_0}^2 + {y_0}^2  {r^2}} \right) = c\\&\Rightarrow \,\,\,{x_0} =  g,\,\,\,{y_0} =  f,\,\,\,r = \sqrt {{x_0}^2 + {y_0}^2  c} \\&\qquad\qquad\qquad\qquad\qquad\quad\;\;= \sqrt {{g^2} + {f^2}  c} \end{align}\]
Thus, given the general form of a circle’s equation, which is
\[{x^2} + {y^2} + 2gx + 2fy + c = 0,\]
we can say that the center of this circle is
\[\left( {{x_0},{y_0}} \right) = \left( {  g,  f} \right),\]
while its radius is
\[r = \sqrt {{g^2} + {f^2}  c} \]
Example 1: A circle is centered at \(\left( {3,  2} \right)\) and has a radius of 4 units. Write its equation in the general form.
Solution: We write the equation of the circle using its center and radius, and then rearrange to the general form:
\[\begin{align}&{\left( {x  3} \right)^2} + {\left( {y  \left( {  2} \right)} \right)^2} = {4^2}\\&\Rightarrow \,\,\,{\left( {x  3} \right)^2} + {\left( {y + 2} \right)^2} = 16\\&\Rightarrow \,\,\,{x^2}  6x + 9 + {y^2} + 4y + 4 = 16\\&\Rightarrow \,\,\,{x^2} + {y^2}  6x + 4y  3 = 0\end{align}\]
Example 2: Find the center and radius of the circle whose equation is \({x^2} + {y^2}  4x  6y  12 = 0\) .
Solution: Comparing the given equation to the standard equation \({x^2} + {y^2} + 2gx + 2fy + c = 0\) , we note that
\[\begin{align}&2g =  4,\,\,\,2f =  6,\,\,\,c =  12\\&\Rightarrow \,\,\,g =  2,\,\,\,f =  3,\,\,\,c =  12\end{align}\]
Thus, the center of the circle is
\[\left( {  g,  f} \right) = \left( {2,3} \right),\]
while its radius is
\[\begin{array}{l}r = \sqrt {{g^2} + {f^2}  c} \\\,\,\, = \sqrt {{{\left( {  2} \right)}^2} + {{\left( {  3} \right)}^2}  \left( {  12} \right)} \\\,\,\, = \sqrt {25} = 5\end{array}\]
Example 3: (a) The equation of a circle is
\[{x^2} + {y^2} + 2gx + 2fy + c = 0\]
\(P\left( {{x_1},{y_1}} \right)\) is a point not lying on this circle. What is the distance of P from the circle’s center?
(b) Find the condition so that a point \(P\left( {{x_1},{y_1}} \right)\) lies outside the circle whose equation is
\[{x^2} + {y^2} + 2gx + 2fy + c = 0\]
How will this condition change if P lies inside the circle?
Solution: Observe the following figure, which shows a circle with center O and a point P not lying on the circle:
The distance OP can be calculated using the distance formula:
\[\begin{array}{l}OP = \sqrt {{{\left( {{x_1}  \left( {  g} \right)} \right)}^2} + {{\left( {{y_1}  \left( {  f} \right)} \right)}^2}} \\\,\,\,\,\,\,\,\, = \sqrt {{x_1}^2 + {y_1}^2 + 2g{x_1} + 2f{y_1} + {g^2} + {f^2}} \end{array}\]
(b) For P to lie outside the circle, the distance OP must be greater than the radius of the circle, which is \(r = \sqrt {{g^2} + {f^2}  c} \). Thus, we have:
\[\begin{array}{l}OP > r\\ \Rightarrow \,\,\,\sqrt {{x_1}^2 + {y_1}^2 + 2g{x_1} + 2f{y_1} + {g^2} + {f^2}}\\\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\; > \sqrt {{g^2} + {f^2}  c} \end{array}\]
Squaring both sides, we have:
\[\begin{array}{l}{x_1}^2 + {y_1}^2 + 2g{x_1} + 2f{y_1} + {g^2} + {f^2}\\\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\; > {g^2} + {f^2}  c\\ \Rightarrow \,\,\,{x_1}^2 + {y_1}^2 + 2g{x_1} + 2f{y_1} + c > 0\end{array}\]
Let us denote the circle’s equation
\[{x^2} + {y^2} + 2gx + 2fy + c = 0\]
by \(S\left( {x,y} \right) = 0\) . Thus, for a point \(P\left( {{x_1},{y_1}} \right)\) to lie outside the circle \(S\left( {x,y} \right) = 0\), the required condition is
\[S\left( {{x_1},{y_1}} \right) > 0\]
Similarly, for \(P\left( {{x_1},{y_1}} \right)\) to lie inside \(S\left( {x,y} \right) = 0\) , the required condition is
\[S\left( {{x_1},{y_1}} \right) < 0\]
Of course, if \(P\left( {{x_1},{y_1}} \right)\) on the circle, then \(S\left( {{x_1},{y_1}} \right) = 0\), as the coordinates of P satisfy the circle’s equation.
Example 4: The equation of a circle is
\[{x^2} + {y^2} + 2x + 4y  11 = 0\]
Where do the points \(P\left( {2,4} \right)\) and \(Q\left( {0,0} \right)\) lie in relation to this circle?
Solution: Represent the equation of the circle by \(S\left( {x,y} \right) = 0\). We substitute the coordinates of P and Q in the expression \(S\left( {x,y} \right)\):
\[\begin{align}&S\left( {2,4} \right)= {2^2} + {4^2} + 2\left( 2 \right) + 4\left( 4 \right)  11\\&\qquad\quad= 4 + 16 + 4 + 16  11 = 29 > 0\\&S\left( {0,0} \right) = {0^2} + {0^2} + 2\left( 0 \right) + 4\left( 0 \right)  11\\&\qquad\quad=  11 < 0\end{align}\]
Clearly, P lies outside the circle, while Q lies inside it.